Impacts of agricultural water interventions on farm income: An example from the Kothapally watershed, India. (June 2015) - Karlberg, L.; Garg, K.K.; Barron, J.; Wani, S.P.
Highlights: AWI resulted in more than a doubling of farm incomes during normal and wet years. With AWI annual incomes fluctuated more compared with the traditional system. The largest economic gains with AWI was observed during the wettest years. Farms with access irrigation benefitted more from AWI compared to other farmers. Economic impacts of AWI needs to be assessed at the farm level. Abstract: Agricultural water interventions (AWI), e.g. in-situ soil and water conservation strategies, irrigation, and damming of rivers to increase groundwater recharge, have been suggested as important strategies to improve yields in tropical agriculture. Although the biophysical implications of AWIs have been well investigated, the coupling between the biophysical changes and the economic implications thereof is less well understood. In this study we translate the results from a hydrological model, SWAT, on crop yields for different cropping systems with and without agricultural water interventions, to hypothetical farm incomes for a watershed, Kothapally, located in Andhra Pradesh, India. It was found that on average, AWI significantly improved farm incomes by enabling the cultivation of a high value crop during the monsoon season (cotton), supplementary irrigated to bridge dry spells and replacing a traditional crop (sorghum), and also by enhancing the capacity to produce dry season, fully irrigated vegetable crops, in this case exemplified by onion. AWI combined with cotton resulted in more than a doubling of farm incomes compared to traditional sorghum-based systems without AWI during normal and wet years (i.e. for 75% of the years). Interestingly, we observed that the difference between the AWI system and the no intervention system was larger during years of high average rainfall compared to dry years. It was also found that access to irrigation was more important for farm income than crop choice and AWI per se, and thus farms with access irrigation benefitted more from AWI compared to farmers lacking access to irrigation. In conclusion, we suggest that in order to assess equity aspects in terms of farm income generation following the implementation of an AWI project, there is a need for income analyses at the farm level, since income estimates at the watershed level may mask important differences in economic benefits between farms.